Development of short amplicon-length PCR-RFLP assay for the detection of Macaca fascicularis meat under complex matrices / Nur Raifana Abdul Rashid - Nur Raifana, Abdul Rashid (2015)
The macaque (Macaca fascicularis) monkeys are the third-largest primate population which are abundant in tropical forests. Despite being the potential carrier of Simian Immunodeficiency, Ebola and Corona viruses as well as religious and wildlife restrictions, macaques have been widely hunted and consumed in many countries. However, in spite of being a potential adulterant of common meat, methods to detect monkey species in food are rarely documented. To fill up this research gap, here a monkey-specific polymerase chain reaction (PCR) assay targeting a short site (120bp) of mitochondrial d-loop gene was described since short-length targets are thermodynamically more stable than the longer ones under compromised states. The theoretical specificity of the primer pair was confirmed against 51 species, including 34 primates of which 13 species were from Macaque genera. The primers were fairly conserved for most of the Macaques but greatly polymorphic for other primates, demonstrating its universal signature for macaque detection. However, due to wildlife restriction, the practical specificity was tested only against 17 terrestrial and aquaticspecies and no cross-species amplification was detected under raw, processed and admixed states. The sensitivity of the assay was 0.0001ng DNA under pure states and 0.1% monkey meat in binary meat mixtures. Finally, the assay was validated by digesting the PCR products with AluI and CViKI-1 and distinctive restriction fingerprints for macaque identification were demonstrated both under raw meat and commercial meatball products. RFLP analysis further authenticated the originality of the PCR product and distinctive restriction patterns were found upon AluI and CViKI-1 digestion. A microfluidic lab-on-a-chip automated electrophoretic system separated the fragments with high resolution. Definitely the assay would be useful to regulatory bodies for food and feeds along with wildlife protection agencies as a reliable authentication technique for the unambiguous tracing of monkey meat under various matrices including the processed food.